The Wonderful Wizard of Oz - Baum, L. Frank (Lahore Readings, 2014)
The Wonderful Wizard of Oz is an American children's novel written by author L. Frank Baum and illustrated by W. W. Denslow, originally published by the George M. Hill Company in Chicago on May 17, 1900. he story chronicles the adventures of a young farm girl named Dorothy in the magical Land of Oz, after she and her pet dog Toto are swept away from their Kansas home by a cyclone. The novel is one of the best-known stories in American literature and has been widely translated. The Library of Congress has declared it "America's greatest and best-loved homegrown fairytale". Its groundbreaking success and the success of the Broadway musical adapted from the novel led Baum to write thirteen additional Oz books that serve as official sequels to the first story.
Keywords: Wizards -- The Journey to the Great Oz -- The Lion Becomes the King of the Beasts